Reproduction strategy of Arabian carpetshark Chiloscyllium arabicum (Gubanov, 1980) in Iraqi marine water - Al-Lammy, Jinan Hassan; Hassan, Sajid Saad; Resen, Amjad Khathim (Iraqi Journal of Aquaculture, 2021)
Reproduction strategy of Arabian carpetshark Chiloscyllium arabicum were studied in Iraqi marine water from January, 2014 to December, 2015. A total of 475 Arabian carpetshark (260 female and 215 male) were cached by trawling net of Bahith Ship (related to Marine Science Center). Results appeared the occurrence of seven length groups and the length-weight relationship was represented by the following equations: W= 0.000006 × L 2.91. Hepato somatic index (HIS) was differ according to maturing conditions of males and females, where highest value (11.906) of HSI for females recorded at October and lowest value (6.908) recorded at June. There were negative correlation between oil ratio of female’s liver and maturing condition. Smallest matured female was 421 ml in total length and 785.23 g in weight, while smallest matured male was 401 in total length and 693.14 in weight. The cycle of gonad maturation was divided into three stages: immature, maturing and mature for males and females. The GSI values were different during study period, where highest values (8.84 and 7.93) for females recorded during April and May respectively and lowest value (0.73) during June, while highest value (6.74) for males recorded during March and lowest value (0.66) during May. Monthly differences in GSI especially for females refers that spawning period extended from May to June. This result can be supported by gonad inspection for males and females.